Aerobryum brevicuspis S.He (Brachytheciaceae), a new species from northern Vietnam. (2nd July 2016) - He, Si; Nguyen, Khang Sinh
Abstract : A new species of Aerobryum Dozy & Molk. (Brachytheciaceae), A. brevicuspis S.He from Lao Cai Province, northern Vietnam is described and illustrated. The new species resembles epiphytic A. speciosum Dozy & Molk. in the presence of pendent, sparsely branched stems, similar shape of leaves and areolation, but differs by its apiculate to cuspidate leaf apices, a single, faint or sometimes double costae in branch leaves, rather differentiated alar cells, the presence of a central strand in the stems, and numerous clustered axillary hairs that are often 5-8(-10) cells long.